Proceedings of the Ninth Annual International Conference on International Computing Education Research 2012
DOI: 10.1145/2361276.2361296
|View full text |Cite
|
Sign up to set email alerts
|

Is iteration really easier to learn than recursion for CS1 students?

Abstract: There is general consensus that recursion is difficult to learn, which may be meant to imply that novice students are more at ease with iteration --- probably a widespread perception of students themselves. However, three years of investigation in a context where recursion is introduced earlier than iteration, as well as control experiments for a standard imperative-first introduction to programming, have provided no evidence that students make more progress with iteration than they do with recursion. More spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Gunion and her collaborators studied elementary and middleschool students in an extracurricular program focusing on recursion and found that the activities improved student interest in computing [4]. A study focusing on whether to teach iteration or recursion first noted that the motivation levels of the two populations had differed, making definitive conclusions difficult to draw [7]. Researchers involved in the Game2Learn project directly considered motivation in creating and measuring the impact of a game for learning recursion [3].…”
Section: Amber Settlementioning
confidence: 99%
“…Gunion and her collaborators studied elementary and middleschool students in an extracurricular program focusing on recursion and found that the activities improved student interest in computing [4]. A study focusing on whether to teach iteration or recursion first noted that the motivation levels of the two populations had differed, making definitive conclusions difficult to draw [7]. Researchers involved in the Game2Learn project directly considered motivation in creating and measuring the impact of a game for learning recursion [3].…”
Section: Amber Settlementioning
confidence: 99%
“…Generally, students have difficulties with recursion [3,6,7], especially identifying base cases [3] and thus some researchers argue that "it is sensible pedagogical practice to base understanding of recursive flow of control on understanding iterative flow of control" [6]. Some other researchers, though, reach the opposite results [11] and one study even concluded that students favor recursion when doing a task such as searching a linked list for a given value and comprehend better recursive code for this and a similar task [1] although the latter was in turn contradicted by a similar more recent study [9].…”
Section: Methodsmentioning
confidence: 99%
“…Novice understanding of programs has been explored from a variety of perspectives, among them: interpreting students' ways of classifying code fragments based on perceived similarities and differences [365]; categorizing novices' mental models of the notional machine underlying imperative [33] and recursive [307] computations, as well as comparing students' mastery of recursion vs. iteration [237]; assessing the understanding of conditionals, loops and nested loops [155,48]; analyzing the relations between students' performance and their annotations in the exam papers [223], and finally comparing block versus textual representations of programs [385].…”
Section: Program Comprehension Activitiesmentioning
confidence: 99%